2018
DOI: 10.1002/clc.22891
|View full text |Cite
|
Sign up to set email alerts
|

What the Women's Health Initiative has taught us about menopausal hormone therapy

Abstract: Our understanding of the complex relationship between menopausal hormone therapy (MHT) and cardiovascular disease (CVD) risk has been informed by detailed analyses in the Women's Health Initiative (WHI), the largest randomized, placebo-controlled trial evaluating MHT in postmenopausal women. Although the WHI demonstrated increased risk of CVD events with MHT in the overall cohort, subsequent secondary analyses demonstrated that these risks were influenced by the woman's age and time since menopause, with lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(38 citation statements)
references
References 44 publications
0
38
0
Order By: Relevance
“…Several studies have criticized the WHI for prematurely drawing conclusions on the safety profile of estrogen and progesterone replacement therapy among postmenopausal women . For example, the WHI published that HRT in postmenopausal women exhibited a significant increase in risk for cardiovascular disease (CVD); however, the study failed to recognize and highlight the influence of age and onset of menopause in this population of women.…”
Section: Safety Of Hormone Replacementmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have criticized the WHI for prematurely drawing conclusions on the safety profile of estrogen and progesterone replacement therapy among postmenopausal women . For example, the WHI published that HRT in postmenopausal women exhibited a significant increase in risk for cardiovascular disease (CVD); however, the study failed to recognize and highlight the influence of age and onset of menopause in this population of women.…”
Section: Safety Of Hormone Replacementmentioning
confidence: 99%
“…For example, the WHI published that HRT in postmenopausal women exhibited a significant increase in risk for cardiovascular disease (CVD); however, the study failed to recognize and highlight the influence of age and onset of menopause in this population of women. A second analysis was conducted on the dataset and showed that CVD events with postmenopausal women on HRT were at significantly less risk than initially described, even suggesting that the risk of perimenopausal women on HRT had low risk of CVD events and all‐cause mortality was not increased . Furthermore, in response to the results shown by the WHI, two studies, KEEPS and ELITE, were published with the purpose of evaluating the HRT safety in early postmenopausal women.…”
Section: Safety Of Hormone Replacementmentioning
confidence: 99%
“…The usage of MHT was significantly affected, with reduced use of oral formulations [40] and an increase in transdermal MHT [41]. Nevertheless, it should be acknowledged that the previous observational studies were in younger participants, who largely had menopausal symptoms, which the majority in the WHI study did not, and the age of the WHI participants was older than the mean age of menopause in Europe or North America, 51 years [37].…”
Section: Menopausal Hormonal Therapymentioning
confidence: 97%
“…The first phase (pre-2002) was characterised by the supposition that the benefits of MHT outweighed the risks, and it was widely used for prevention and treatment of menopausal symptoms. It was therefore one of the most prescribed medications at the time, peaking in 2001, with 40% of postmenopausal women using MHT [36,37]. Observational studies of the time suggested a potential benefit to cardiac health (with up to a 50% reduction in coronary heart disease).…”
Section: Menopausal Hormonal Therapymentioning
confidence: 99%
“…MHT was widely used in the 1980s and 1990s for the prevention of symptoms associated with the menopause, such as hot flushes, night sweats and sleep disturbance, with the widely prevailing view that prevention of cardiovascular disease and osteoporosis were additional benefits [7,8]. The rationale for such an approach was an evidence-base consisting principally of observational studies, in which the use of hormone replacement therapy (as it was known at that time) was associated with generally improved health outcomes, particularly in relation to cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%